INOVASI KEPEMIMPINAN KEPALA SEKOLAH BERASASKAN TRILOGI KEPEMIMPINAN KI HAJAR DEWANTARA DALAM UPAYA MENINGKATKAN KOMPETENSI GURU DI GUGUS 2 NANGGULAN - Agnes Kristini; Agus Sri Purnami; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe leadership innovations for elementary school principals in Cluster 2 Nanggulan based on the Ki Hajar Dewantara leadership trilogy. This study uses a qualitative approach. Data collected by interview, observation, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The validity of the data was carried out by means of source triangulation and technique triangulation. The results of the study show that the leadership innovation of the elementary school principal in Cluster 2 Nanggulan based on the Ki Hajar Dewantara leadership trilogy in an effort to improve teacher competence is that the principal also conducts a self-development program to increase his competence in the hope that he will be emulated by other teachers whose teachers then take part in the improvement program. competence, school principals are involved in teacher competency improvement programs in the form of creating certain situational conditions so that teachers can easily participate in competency improvement programs, and school principals provide motivational encouragement so that teachers can be enthusiastically interested in participating in competency improvement programs for example by giving small rewards. The inhibiting factor in the implementation of elementary school principal leadership innovations in an effort to improve teacher competence based on the Ki Hajar Dewantara leadership trilogy in Cluster 2 Nanggulan is the teacher's mindset which is difficult to change teacher teaching habits to use more effective and efficient teaching methods. Supporting factors in the implementation of elementary school principal leadership innovations in an effort to improve teacher competence based on the Ki Hajar Dewantara leadership trilogy in Cluster 2 Nanggulan is the organizational structure of the principal who is the highest peak position in the school able to make teachers obey or consider policies and suggestions from the principal to improve the ability of the teacher itself. The achievement of school principals in getting teachers to make efforts to increase pedagogic competence, social competence, personal competence, and professional competence with the kihajar dewatara leadership principle, namely setting an example, providing motivation and moving teachers, and giving encouragement to teachers is 64.32%. Setting an example, motivating and moving teachers, and giving encouragement to teachers is not always successful in increasing the competence of teachers. Teachers may not follow the example of the principal, teachers may not listen to the motivation of the principal, teachers may not be successful in being encouraged so that they are less interested in improving their poaedagogic competence, professional competence, personal competence, and social competence.